2010
DOI: 10.1073/pnas.1010819107
|View full text |Cite
|
Sign up to set email alerts
|

α-Dystrobrevin-1 recruits α-catulin to the α 1D -adrenergic receptor/dystrophin-associated protein complex signalosome

Abstract: α 1D -Adrenergic receptors (ARs) are key regulators of cardiovascular system function that increase blood pressure and promote vascular remodeling. Unfortunately, little information exists about the signaling pathways used by this important G protein-coupled receptor (GPCR). We recently discovered that α 1D -ARs form a “signalosome” with multiple members of the dystrophin-associated protein complex (DAPC) to become functionally expressed at the plasma membrane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 45 publications
(68 reference statements)
2
58
1
3
Order By: Relevance
“…The anti-␣-catulin antibodies used in the present study were made by our group and have been validated in other studies (18). Although Lyssand et al (36) showed that ␣-catulin interacts with ␣-and ␤-dystrobrevin 1 in tissue culture cells, it was not clear from those studies whether lack of ␣-catulin disrupts the integrity and localization of the DAPC. Given that disrupted integrity of the DAPC is extensively documented as a cause of muscular dystrophy, addressing this question is important for understanding the pathogenesis of muscular dystrophy.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The anti-␣-catulin antibodies used in the present study were made by our group and have been validated in other studies (18). Although Lyssand et al (36) showed that ␣-catulin interacts with ␣-and ␤-dystrobrevin 1 in tissue culture cells, it was not clear from those studies whether lack of ␣-catulin disrupts the integrity and localization of the DAPC. Given that disrupted integrity of the DAPC is extensively documented as a cause of muscular dystrophy, addressing this question is important for understanding the pathogenesis of muscular dystrophy.…”
Section: Discussioncontrasting
confidence: 39%
“…Lyssand et al reported that ␣-catulin interacts with dystrobrevin in a human embryonic kidney cell line (36). They speculated that the C terminus of dystrobrevin mediates the interaction with ␣-catulin because ␣-catulin is only co-purified with the isoform that retains the extra C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…2) (Adams et al, 1995;Ahn et al, 1996;Chen et al, 2006). These syntrophins interact with a 1D AR and collectively facilitate the functional expression of the receptor at the membrane, promoting a 1D AR-mediated phosphatidylinositol hydrolysis, ERK1/2 phosphorylation, and Ca 21 mobilization Lyssand et al, 2008Lyssand et al, , 2010Lyssand et al, , 2011. Neither g 1 -syntrophin nor g 2 -syntrophin comparably bind a 1D AR, despite containing one PDZ domain and a PH domain, and their potential role in GPCR regulation remains uncertain .…”
Section: Additional Gpcr-interacting Pdz Proteinsmentioning
confidence: 99%
“…Finally, these interactors form multimolecular networks. For example, α-catulin, which is a general interactor for α-dystrobrevin-1 also binds to syntrophin, utrophin, β-dystrobrevin (a product of a different gene from that encoding α-dystrobrevin-1) and Arhgef5 (Lyssand et al, 2010). Our studies have identified that Arhgef5 is also a phosphodependent α-dystrobrevin-1 ligand.…”
Section: Discussionmentioning
confidence: 86%
“…The one protein from this group that we considered further was the deubiquitinating enzyme Usp9x (Théard et al, 2010), which was highly enriched in α-dystrobrevin-1 complexes (79 peptides recovered) and virtually missing in the control purification. The remaining eight proteins comprised six components of the DGC [three syntrophin isoforms, two dystrobrevin isoforms and utrophin (Sunada and Campbell, 1995)]; α-catulin, which we and others have previously shown to bind to α-dystrobrevin (Lyssand et al, 2010;Oh et al, 2012); and liprin-α1, a scaffold protein previously shown to interact with α-catulin (Lyssand et al, 2010;Spangler and Hoogenraad, 2007;Spangler et al, 2011) (Fig. 3B).…”
Section: Identification Of α-Dystrobrevin-1-interacting Proteinsmentioning
confidence: 99%